Combinations of Cannabinoids with Silver Salts or Silver Nanoparticles for Synergistic Antibiotic Effects against Methicillin-Resistant Staphylococcus aureus - John Jackson; Ali Shademani; Manisha Dosanjh; Claudia Dietrich; Mark Pryjma; Dana M. Lambert; Charles J. Thompson (MDPI AG, 2024)
Silver has been shown to improve the antibiotic effects of other drugs against both Gram- positive and -negative bacteria. In this study, we investigated the antibiotic potential of cannabidiol (CBD), cannabichromene (CBC) and cannabigerol (CBG) and their acidic counterparts (CBDA, CBCA, CBGA) against Gram-positive bacteria and further explored the additive or synergistic effects of silver nitrate or silver nanoparticles using 96-well plate growth assays and viability (CFUs- colony-forming units). All six cannabinoids had strong antibiotic effects against MRSA with minimal inhibitory concentrations (MICs) of 2 mg/L for CBG, CBD and CBCA; 4 mg/L for CBGA; and 8 mg/L for CBC and CBDA. Using 96-well checkerboard assays, CBC, CBG and CBGA showed full or partial synergy with silver nitrate; CBC, CBDA and CBGA were fully synergistic with silver nanoparticles against MRSA. Using CFU assays, combinations of CBC, CBGA and CBG with either silver nitrate or silver nanoparticles, all at half or quarter MICs, demonstrated strong, time-dependent inhibition of bacterial growth (silver nitrate) and bactericidal effects (silver nanoparticles). These data will lead to further investigation into possible biomedical applications of specific cannabinoids in combination with silver salts or nanoparticles against drug-resistant Gram-positive bacteria.